Vetcaresys: Web-Based Vet Management System in Misamis Occidental with Mapping - Judielyn Lasagas Cualbar; Loelyn T Ates; Zhiena May U Larotin; Julliebert M Simbajon; Edjenn L Suan; Rica May C Telecio (MDP Student Conference, 2026)
The growing number of pet owners and demand for veterinary services have exposed the limitations of manual, paper-based clinic operations, especially in rural areas such as Misamis Occidental. Many veterinary clinics face challenges including disorganized records, inefficient appointment scheduling, and limited online visibility. To address these issues, this study developed VetCareSys, a web-based veterinary management system that supports digital record management, appointment scheduling, automated SMS and email notifications, and clinic location mapping. The system aims to improve efficiency, accuracy, and accessibility of veterinary services while supporting digital transformation aligned with Sustainable Development Goals (SDG) 3, 9, and 11. VetCareSys was evaluated using ISO/IEC 25010 standards through structured questionnaires during pilot testing. The evaluation results showed an overall mean rating of “Excellent,” indicating high levels of functionality, usability, reliability, efficiency, maintainability, portability, and security. These results demonstrate that VetCareSys effectively streamlines clinic operations and enhances service delivery.